PERAN GURU PIAUD DALAM MENANAMKAN BAHASA INDONESIA PADA ANAK USIA DINI - Arni Mahyudi; Mahlida Farina (Yayasan Pendidikan Literasi Borneo, 2025)
The use of good and correct Indonesian in early childhood is increasingly important amidst the prevalence of code-mixing, slang, and the influence of family and social environments that do not always use standard language. This situation demands a significant role from Early Childhood Islamic Education (PIAUD) teachers as primary role models in shaping children's language habits. This study aims to describe how PIAUD teachers instill good and correct Indonesian through daily learning practices. Data were collected through observation, interviews, and documentation of PIAUD teachers in Kandangan District. The results indicate that teachers play a crucial role in language habituation through story reading, role-playing, structured conversations, the use of educational songs, and the practice of using complete sentences in daily interactions. However, the study also identified various obstacles such as limited supporting learning media and a lack of ongoing training. Children who receive consistent language stimulation demonstrate better development in listening, speaking, and sentence construction, while children who receive less stimulation experience communication barriers. This study concludes that the success of instilling good and correct Indonesian language is highly dependent on the role model, consistency, and pedagogical strategies of PIAUD teachers, which need to be supported through training, supervision, provision of media, and collaboration between schools and parents.